Development of new braided fibrous materials for retrofitting of masonry walls - Cunha, Fernando Eduardo Macedo (2013)
The most recent earthquakes in Turkey (Kocaeli 1999, Duzce 1999, Bingol 2003), Italy (L'Aquila, 2009) and Spain (Lorca, 2011) demonstrated the vulnerability of non-loadbearing unreinforced masonry walls acting as infill of reinforced concrete frames. To address this issue, the main focus of this work was to develop a fibrous structure that will provide very good adhesion with the cement mortar and will present excellent ductility in order to sustain the structure of masonry walls after a seismic event, avoiding complete splitting and collapse. Different fibrous structures were produced with different surface characteristics (height of surface undulations and spacing between them). The adhesion between these braided structures and cement mortar was characterized using pull-out tests and according to the experimental results, the braided structures with polyester braids as braiding yarn and, produced using optimized process parameters showed excellent adhesion with cement mortar, leading to complete breakage of these structures before being pulled out from the cement mortar.